Ultrasonographic-based predictive factors influencing successful return to racing after superficial digital flexor tendon injuries in flat racehorses: a retrospective cohort study in 469 Thoroughbred racehorses in Hong Kong - Alzola, R.; Easter, C.; Riggs, C.M.; Gardner, D.S.; Freeman, S.L. (Wiley, 2018)
Background: Superficial digital flexor tendon (SDFT) injury is an important health and welfare concern in racehorses. It is generally diagnosed with ultrasonography, predictive ultrasonographic features have not been reported. Objectives: To determine ultrasonographic features of forelimb SDFT injury at initial presentation in Thoroughbred racehorses, that could predict a successful return to racing (completing > or = 5 races). Study Design: Retrospective cohort study. Methods: Digitised ultrasonographic images of 469 horses with forelimb SDFT injuries from the Hong Kong Jockey Club (2003-2014) were evaluated, using a previously validated ultrasonographic scoring system. Six ultrasonographic parameters were evaluated (type and extent of the injury, location, echogenicity, cross-sectional area and longitudinal fiber pattern of the maximal injury zone (MIZ)), as well as horse signalment, retirement date and number of races before and after injury. Data was analysed by generalized linear regression with significance at P<0.05. Results: Cases were divided in two groups: 1) For cases of SDFT tendonitis with core lesions, cross-sectional area at the MIZ was the most significant factor determining a successful return to racing (p=0.03). If the lesion was <50% of the total cross-sectional area, horses had 29-35% probability of successfully racing again, but if it was > or > or = 50% this decreased to 11-16%. 2) For cases of SDFT tendonitis without a core lesion, longitudinal fiber pattern at the MIZ best predicted a successful return to racing (P=0.002); if the affected longitudinal fiber pattern was <75% of the total, horses had 49-99% probability of successfully return to racing, but if it was > or = 75% this decreased to 14%. Main Limitations: Prognostic information may not be applicable to other breeds/disciplines. Conclusions: This is the first study to describe ultrasonographic features of forelimb SDFT injuries at initial presentation that were predictive of successful return to racing. The outcomes will assist with early, evidence-based decisions on prognosis in Thoroughbred racehorses.